1992
DOI: 10.1007/bf03190142
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in metabolism of simvastatin by rat hepatic microsomes

Abstract: Metabolism of simvastatin (SV), a new cholesterol-lowering agent, by hepatic microsomes from male and female rats was investigated. After incubation of [14C]-SV with hepatic microsomes, radioactive metabolites were detected by HPLC. The main metabolite was 3' alpha-hydroxy-SV in male rats and the hydroxy open acid form of SV (SVA) in females. The 3"-hydroxy-SV and 3',3"-dihydroxy-SV which were observed in male rats were hardly detected in females. Specific activity for the metabolism of SV in male rats (3.97 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…dose in male and female rats, respectively. These gender differences in the metabolism of SV are consistent with previously published in vitro data (Ohtawa and Uchiyama, 1992), which showed a higher rate of metabolism in males than in female rats. In vivo, a similar trend was observed, and the gender differences have been attributed to the different P450 isozymes responsible (CYP3A in female and CYP2C11 in male rats) for the metabolism of SV (Ishigami et al, 2001).…”
Section: Svasupporting
confidence: 92%
“…dose in male and female rats, respectively. These gender differences in the metabolism of SV are consistent with previously published in vitro data (Ohtawa and Uchiyama, 1992), which showed a higher rate of metabolism in males than in female rats. In vivo, a similar trend was observed, and the gender differences have been attributed to the different P450 isozymes responsible (CYP3A in female and CYP2C11 in male rats) for the metabolism of SV (Ishigami et al, 2001).…”
Section: Svasupporting
confidence: 92%
“…Second, pathophysiological differences between females and males could be a possible reason, since some studies had remarked on the sex differences in statin effects [39][40][41]. Moreover, in some animal studies, statins might have a greater clinical efficacy among males due to differences in the rate of metabolism, depending on sex [42,43]. Several epidemiological studies have reported greater cholesterol reductions by statins among women than men [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Five metabolites 5-9 of SV were identified in rat plasma and urine using gas chromatography-mass spectrometry (GC-MS) [29]. In addition to that work, using HPLC-UV, six other metabolites 10-15 including metabolite 5 were detected in rat hepatic microsomes [30], and using NMR and mass spectroscopy [31] the same were detected in rat liver microsomes (RLMs). Later, Prueksaritanont et al [32] identified another two new metabolites 16 and 17, including three known metabolites 5, 10, and 11 using LC-MS/MS in HLMs.…”
Section: Introductionmentioning
confidence: 88%
“…In order to maximize its excellent cholesterol-lowering effect and minimize its serious side effects, an in-depth study of its metabolism becomes indispensable to understand the mechanisms underlying its pharmacological effects and its potential side effects. Metabolic profiling of SV has been reported in a number of articles using different analytical methods [29][30][31][32][33]. To date, thirteen metabolites of SV have been identified, which are depicted in Figure 2.…”
Section: Introductionmentioning
confidence: 99%